INTERACTION OF H(D,T)O WITH MINERAL ADSORBENTS IN STATIONARY SYSTEMS - PUSHKAREV, Oleksandr; SEVRUK, Iryna; ZUBKO, Oleksandr; DOLIN, Vitaly; DEMIKHOV, Yuri; SKRYPKIN, Vadym (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The theoretical basis of the experiments is the idea that the significant adsorption properties of layered silicates of the montmorillonite and palygorskite groups and clinoptilolite with a developed specific surface due to the dynamic nature of adsorption-desorption processes due to kinetic isotope effects can ensure priority retention of mineral particles of more inert hydroxide groups ОТ– near the adsorption surfaces. Methods. Cherkasy bentonite with a montmorillonite content of 75 % (hereafter montmorillonite), Varvarivska saponite, and Sokyrnytsky clinoptilolite were used for the experiments. Experiments were performed in stationary mode in hermetically sealed containers (two-phase watermineral system). Results. During the first 7 days of interaction of the aqueous and mineral phases, the specific activity of tritium in the working solution decreased by 31.8–69.5 %. Subsequently, during the 92 days of interaction of the aqueous solution of H(D,T)O with mineral adsorbents, the change in the specific activity of tritium did not exceed 2–4 %. At the same time, the initial concentration of deuterium in the working solution of Н(D,Т)О of two-phase water-mineral systems decreased by only 0.8–14 %, ranging from 0.0066 % to 0.0408 %. During the experiment, in closed water-mineral systems, a partial interphase redistribution of the initial stock of hydrogen isotopes, which was accumulated in the initial working solution Н(D,Т)О, took place. In the process of adsorption of the solution by mineral adsorbents, the initial moisture in the mineral phase was replaced by Н(D,Т)О and the content of hydrogen isotopes increased in them. The content of tritium in the adsorbate, depending on the mineral type of the adsorbent, increased by 31.8 to 69.5 %. Concentration of deuterium increased by 10.1–48.6 %, which was due to the different adsorption capacity of mineral adsorbents. Adsorption of the H(D,T)O working solution by mineral adsorbents was accompanied by fractionation of heavy hydrogen isotopes.  Сonclusions. Аs a result of the interaction of the Н(D,Т)О solution with mineral adsorbents, kinetic isotope effects determined the priority retention of more inert hydroxide ОТ-groups than OD- groups near the adsorption surface of mineral particles. Consequently, interphase fractionation of heavy hydrogen isotopes occurred in stationary water-mineral systems. The coefficients of tritium interphase fractionation range from α = 1.26 for palyhorskite to α = 2.96 for clinoptilolite. For deuterium, this indicator is equal to α = 0.89 for clinoptilolite and to α = 1.10 for saponite.
Keywords: fractionation; tritium; deuterium; montmorillonite; sepiolite; saponite; palyhorskite; clinoptilolite